'One of the oldest states in Europe has never suppressed any nation'. The minority treaty, nationalist indignation and the foundations of interwar ethnic democracy in Poland. Issue 4 (30th September 2021) - Marzec, Wiktor
Abstract: This article investigates the internal impact of the Minority Treaty of Versailles, regulating minority rights and protection in the emerging interwar Polish state. The parliamentary debate on the Treaty was a critical juncture structuring the political sphere and arguably fostered the birth of 'ethnic democracy' in Poland. Performing a sequential analysis of the debate, I study the reconfiguration of political positions which locked the actors into their strategic entrenchments. Unexpectedly, the nationalist right defended the treaty because of their involvement in the Versailles negotiations. The left tried to delegitimize the treaty and simultaneously tip the scales of the domestic politics in favour of the minorities. This shifted the levers of implicit assumptions about the political community and effectively blocked the political efficacy of the treaty on the domestic level. Such refraction effects must be considered when one is studying convergence, diffusion and the role of international agreements and pressures.